Mathematics that We Know and Use - RAJPUT, ANUP KUMAR (THE PRIMARY TEACHER, 2016)
People, generally, have a wrong notion that mathematics is a difficult subject and believe that it is impossible to enjoy it. It is a fact that math is a part of everyday life. The understanding of mathematics comes very early and naturally in life. In other words, every one can enjoy, engage with, and relax with mathematics. Mathematics is much more — in fact, a lot more than numbers and working algebra formulas. These aspects sharpen the mathematical skills that one may already posses, just as speaking and writing is learned more by language skills. Many subjects and aspects are so deeply integrated with mathematics that it is hard to define it. Mostly in schools, one definition of mathematics prominently learnt is, “Mathematics is the study of quantities and relations through the use of symbols, numbers and rules”. This article will help you to appreciate how mathematics is not only a part of you but of animals as well. Secondly, you will see how mathematical problems can be solved faster and with ease. You will also see how to skip the steps entirely and still find accurate or workable solutions to mathematical problems, perhaps without even using a pen and paper. You will, finally, realise that you have known mathematics and that it is an imperceptible part of your daily life.